A leitura literária de clássicos, dinamizada a partir de dois ambientes: a biblioteca e a sala de aula - Silva, Karla Rodrigues da (2021)
Dissertation developed during the Professional Masters in Teaching in Basic Education of the Postgraduate Program Stricto Sensu of the Center for Teaching and Research Applied to Education (CEPAE) of the Federal University of Goiás (UFG), between 2019 and 2021. The main. The objective of this research was to identify possibilities to encourage reading classics in literature, through activities involving students from the 5th year of Elementary School and professionals working in the library and in the classroom. The theoretical foundations are studies by: Bloom (2001), Calvino (1993), Campello (2002), Candido (2004), Colomer (2017), Faguet (2011), Freire (1989), Machado (2002), Zilberman (2003), between others. This is a quantitative and qualitative research, developed at Cepae-UFG. Due to the pandemic context of Covid-19, the field research was carried out through remote teaching, based on the reading of narratives by Machado de Assis and mediated discussions, which could be extended to more students, due to the use of digital platforms. The results indicate that it is possible to carry out actions to encourage literary reading, aiming at educating the reader, and that they can become even more productive when there is a partnership between librarians and teachers. The Educational Product is a “Literary Biblio-car”, a proposal for a traveling library, with a view to favoring activities to promote and value literary reading.